A Series of Propofol Analogs Design by Targeting Pentameric Ligand-gated Ion Channel In Silico Method - Gao, Jing; Wu, Xiao-Hui; Dong, Wei-Li; Wang, Shu-Qing (Protein and Peptide Letters, 2013)
The crystal complex propofol/GLIC (the bacterial homologue from Gloeobacter violaceus) recently determined also showed sensitivity to general anesthetics, belonging to the pLGIC (pentameric ligand-gated ion channels) family as a homopentameric member, which are potentiated and inhibited by general anesthetics and mimic changes elicited by anesthetics in physiologic targets as ion channels, providing the useful information for general anesthetics and allosteric modulators design. Thirteen active compounds selected from the previous data sets are used as reference and seed structures for developing novel general anesthetics via the scoring function of lead optimization using pharmacophoric & shape similarity integrated in Muse™ molecular design workflow. Autodock4.0 is validated its accuracy by two computational procedures and used for docking calculations in this study. Finally, the top ten invented propofol analogs reported here exhibit more favorable binding energies geometric matching than propofol. Especially, the comp#1 fits the binding site well in geometric shape with the lowest binding energy than any other compounds, and makes the hydrophobic interaction with the binding site formed by M4 helixes and lipids of receptor as well. More importantly, the interactions between ligand and lipids caused by general-anesthetic binding would be specially considered in novel general anesthetic design. accordingly, the findings reported here may provide useful insights for discovering more effective general anesthetics.
Keywords: drug design